Maternal and fetal outcome among abruptio placentae cases at a rural tertiary hospital in Karnataka, India: a retrospective analysis - Shrivastava, Vartika; Kotur, Pushpa; Jauhari, Abhinav (International Journal of Research in Medical Sciences, 2017)
Background: Placental abruption complicates about 1% of pregnancies and is a leading cause of vaginal bleeding in the latter half of pregnancy. It is also an important cause of perinatal mortality and morbidity. The maternal effect of abruption depends primarily on its severity, whereas its effect on the fetus is determined both by its severity and the gestational age at which it occurs. The Diagnosis was confirmed on the presence of retroplacental clot, which was used to estimate the amount of bleeding and severity of abruption. Patients were managed according to the fetal and maternal conditions and ultrasonography. Methods: The study was carried out for a period of two years from 1st July 2012 to 30th June 2014. The study population included all cases presenting with ante partum hemorrhage to the Department of Obstetrics and Gynecology during the study period. Subjects selected for the study were all cases diagnosed as having abruptio placentae. Results: Total number of women admitted in labor ward between 1st July 2012 to 30th June 2014 was 4956. Among these 138 had abruption placenta. Majority of patients were in the age group 25-30 years. Incidence was higher in multi-parous. Spontaneous vaginal delivery was the mode in most patients (~74%). Major maternal complication seen was Shock, followed by postpartum hemorrhage, altered coagulation profile and renal failure. Eighty four (62.3%) women delivered alive babies while 52(37.7%) were stillborn. Out of these 86 alive born babies four died in early neonatal period due to prematurity. Overall perinatal mortality was 40.5%. Conclusion: In our setup, frequency of abruptio placenta is comparable with local and international literature. Abruptio placenta is associated with high rate of maternal and fetal morbidity and mortality, Because of this association, the conditions predisposing it should be carefully evaluated in order to reduce the occurrence of placental abruption. Unfortunately neither accurate prediction nor prevention of abruption is possible at the present time. Despite advances in medical technology, the diagnosis of abruption is still a clinical one.